2016
DOI: 10.1186/s12889-016-3495-x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to malaria diagnosis and treatment guidelines among healthcare workers in Ogun State, Nigeria

Abstract: BackgroundMalaria case management remains a vital component of malaria control strategies. Despite the introduction of national malaria treatment guidelines and scale-up of malaria control interventions in Nigeria, anecdotal evidence shows some deviations from the guidelines in malaria case management. This study assessed factors influencing adherence to malaria diagnosis and treatment guidelines among healthcare workers in public and private sectors in Ogun State, Nigeria.MethodsA comparative cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 17 publications
(18 reference statements)
12
55
5
2
Order By: Relevance
“…Despite reports of malaria decline in different parts of sub-Saharan Africa, reports indicate varying level of adherence to malaria diagnosis test and treatment guidelines [15][16][17], as well as lack of awareness on the availability of malaria diagnosis and treatment guidelines [16]. Furthermore, in many settings, national programs have devoted much in making sure that RDT is available in peripherals, and compliance to negative results will need to improve to prevent mismanagement of patients and overprescribing of anti-malarial drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite reports of malaria decline in different parts of sub-Saharan Africa, reports indicate varying level of adherence to malaria diagnosis test and treatment guidelines [15][16][17], as well as lack of awareness on the availability of malaria diagnosis and treatment guidelines [16]. Furthermore, in many settings, national programs have devoted much in making sure that RDT is available in peripherals, and compliance to negative results will need to improve to prevent mismanagement of patients and overprescribing of anti-malarial drugs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In another related study conducted in sub-Saharan Africa, the following factors were reported as predictors of compliance with RDT negative results: patient expectations, work experience, skepticism of result, health workers cadres and perception [16]. Another related study conducted in Nigeria reported that access to treatment guidelines; availability of test kit and training on malaria case management were not associated with compliance with RDT result [22]. This study's analysis suggests that RDT stock-out was not significantly associated with compliance with test result.…”
Section: Discussionmentioning
confidence: 97%
“…Whilst it is therefore not possible to draw direct conclusions from these data about the causes of ACT non-prescription, a number of possible explanatory factors were suggested by Burchett et al [19], including motivation to perform well in a study context, stability of ACT supplies, and local preferences for different types of antimalarials. More broadly, other previous work has identified some factors that are associated with non-adherence to test results and/ or treatment guidelines, including distrust in the test or test result [36][37][38][39], patient demands or preferences for a particular medication [19,[40][41][42][43], perceptions of low drug efficacy [41], staff workload [44], financial incentives [42], level of health care worker [41,45,46], affordability and accessibility of non-recommended therapies [47,48], and rationing of medications [19,49]. Stock-outs of weightspecific drug packs can also lead to inappropriate prescription of medications [45,50], whilst lack of knowledge on how to prescribe second-line drugs can lead to not prescribing them at all [51].…”
Section: Discussionmentioning
confidence: 99%
“…Stock-outs of weightspecific drug packs can also lead to inappropriate prescription of medications [45,50], whilst lack of knowledge on how to prescribe second-line drugs can lead to not prescribing them at all [51]. The availability of antimalarials has been shown to influence prescribing patterns [45,47,52], and health care workers are often restricted to prescribing what is available to them. With the exception of Tanz1 which evaluated "real-world" mRDT implementation, ACT stocks were generally maintained in the study areas during the primary ACT Consortium studies; it is possible, however, that some combination of these factors, which are more common outside of optimal study conditions, contributed to the prescribing behaviours seen in this analysis.…”
Section: Discussionmentioning
confidence: 99%